Impact of Different Electrolytes on the Machining Rate in ECM Process - K. G. Saravanan; R. Prabu; A. R. Venkataramanan; Eden Tekle Beyessa (Advances in Materials Science and Engineering)
Electrochemical machining is a nonconventional machining process in which the metal removal is achieved by the electricity and chemical solution known as an electrolyte. It is the reverse electrolysis process where the application of electricity facilitates the current travel in between anode and cathode. The mechanism of the ion movement is similar to the electrolysis process. Electrochemical machining (ECM) is a type of advanced machining process which employs electricity to perform the machining process on the workpiece. It is also known as a reverse electroplating process where metal removal is achieved instead of metal deposition on the metal surface. There are various parameters that affect the metal removal process in the ECM process, such as electrolyte, power supply, workpiece material, and tool material. The electrolyte is one of the key factors impacting the machining rate, surface finish, and reliability of the produced parts. In this project, a brief study is carried out regarding the electrochemical process and the electrolytes where the properties, functions, merits, and demerits are evaluated. The impact of the various electrolytes and their suitability for machining of various metals is also discussed. The findings of the effect produced by using the mixture of the electrolyte in the electrochemical machining process are discussed in this project. The effects of the complexing agents on the electrolyte and the electrochemical process as a whole are also reviewed.